A Suggested Imagination for the Strategic Planning to Manage the Educational Crises. "A field study from the point of the initial stage Schools headmasters in Damascus" - Ksheek, Mona; Moshly, Nesreen (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research aimed to create a Suggested Imagination to active the roll of the Strategic Planning that the initial stage Schools headmasters in Damascus must use to manage the educational crises in their institution. The research society contain all the initial stage schools headmaster in Damascus City, that they are (316) headmasters, and the research was implicated on a random sample contain (242) member. The researcher depended on the analytical descriptive method, and used a questionnaire to collect information, so he repaired two questionnaires, the first one about the most crises the initial stage schools suffer, and the second contains (58) items about the proceedings which the headmaster must do them, and it divided to for fields, they are: before the happened of the crisis, planning to management the crisis, management the crises, the prevention and the capitalize of the crises after it happened. The results showed that the initial stage Schools headmasters are suffering from crises related to the students, the curriculum, and the teachers, and their practice degree for the subtrahend proceedings quadrated to the questionnaire is a median degree, that is subpoenaed drawing up a suggested imagination to become the Strategic Planning is the method which used to manage the educational crises and obviated them.